Evaluation Method for Tourism Development Focused on Poverty Alleviation - Simorangkir, Cavin Ornando; Sabrina Rahmadhanty Maghfira (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2024)
This study aims to evaluate the effectiveness of tourism development in poverty alleviation, focusing on systems and policies implemented in Indonesia. Using a qualitative approach, document analysis was employed to review various policies, case studies, and strategies implemented in several countries/regions. The data used include scholarly articles, regulations, written policies, and notes from stakeholders relevant to tourism development and poverty alleviation. The document analysis results indicate that pro-poor tourism development policies require a holistic and contextual evaluation, considering local conditions, social capital, and impact mapping. This study also explains relevant and contextual evaluation methods for pro-poor tourism related to regional development policies, including evaluation of policy formulation, implementation, and development outcomes. Thus, this research is expected to make a significant contribution to expanding the understanding of tourism development evaluation focused on poverty alleviation and to provide more effective and targeted policy recommendations.